Identification of genes associated with disc degeneration using bioinformatics. (July 2015) - Ji, S-C; Han, N; Liu, Y; Li, G; Sun, Z; Li, Z
Abstract Intervertebral disc degeneration is a common orthopedic disease that has been recognized as the major cause of low back pain. About 80% of the population is affected by this disease. We explored molecular mechanisms of disc degeneration and identified the genes associated with the disease. The transcription profile of GSE34095 was downloaded from Gene Expression Omnibus database with three degenerative disc samples and three healthy disc samples. Gene ontology and pathway enrichment analysis were performed. We constructed a protein-protein interaction (PPI) network and a transcription factor (TF) target network. Differentially expressed genes (DEGs) in normal and disc degeneration samples were identified including 243 up-regulated genes and 351 down-regulated genes. Meanwhile, seven Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were obtained by mapping the 594 DEGs to the KEGG and we found that the calcium signaling pathway was the most significant for developing disc degeneration. The pathways interaction network analysis showed that the adherens junction pathway interacted with other six pathways. In addition, the top five genes, FYN, PRKCD, YWHAB, YWHAZ and AR, with a high degree of interaction of 7, 4, 4, 4 and 4, respectively, were related to the disc degeneration in the PPI network. Furthermore, transcription factors including TFAP2A, E2F4, SP3 and AR had the potential to regulate disc degeneration through the mitogen-activated protein kinase, vascular endothelial growth factor and p53 pathways. The genes and pathways that we identified may be involved in disc degeneration.